The impossible feast of the uncanny technowoman : a plural feminist cyborg writes of the possibilities for science fiction and potent body politics : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Manawatū Campus, New Zealand - Connor, Geneva (Massey University, 2019)
This research embodies Donna Haraway’s (1991) feminist cyborg as a potent political figure for women and their bodies in the 21st century West. The violences done to women all too often define them (Malabou, 2011), confining them to the heterosexual matrix characterised by their objectification and ‘excesses.’ The multiplicities and pluralities of ‘woman’ disrupt traditional psychological science that counts and categorises. Re-routing psychology through the hybridity and non-fixity of the science fiction genre, new possibilities for psychological knowledge production emerge, including figures (such as cyborgs), art installations and hyperdimensional arachnids through which to think new thoughts (Haraway, 2016). Through the figure of a feminist cyborg, ‘woman’ can be understood as politically potent through her multiplicities, partialities, simultaneities and contradictions. After rendering Haraway’s feminist cyborg through the science fiction genre, the thesis takes on a creative form to re-think the notion of apocalypse, re-theorise the uncanny, then explore a potently networked series of figures, internet users and movements (such as Human Barbies, internet folklore, pro-rape forums) that structure women’s bodies in ways that re-assert the heterosexual matrix, as well as in ways that re- build women outside of the heterosexual matrix. Re-figuring ‘woman’ outside of the heterosexual matrix could perhaps open new spaces in which to think women’s body politics differently in perpetually networked, ever-expanding technoworlds.
Keywords: Women in technology; Science fiction; Psychological aspects; Women; Violence against; Feminist theory; 520502 Gender psychology